Erythropoietin in Lupus: Unanticipated Immune Modulating Effects of a Kidney Hormone - Eswarappa, Meghana; Cantarelli, Chiara; Cravedi, Paolo (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a multiorgan autoimmune disease with variable clinical presentation, typically characterized by a relapsing-remitting course. SLE has a multifactorial pathogenesis including genetic, environmental, and hormonal factors that lead to loss of tolerance against self-antigens and autoantibody production. Mortality in SLE patients remains significantly higher than in the general population, in part because of the limited efficacy of available treatments and the associated toxicities. Therefore, novel targeted therapies are urgently needed to improve the outcomes of affected individuals. Erythropoietin (EPO), a kidney-produced hormone that promotes red blood cell production in response to hypoxia, has been shown lately to also possess non-erythropoietic properties, including immunomodulatory effects. In various models of autoimmune diseases, EPO limits cell apoptosis and favors cell clearance, while reducing the proinflammatory cytokines and promoting the induction of regulatory T cells. Notably, EPO has been shown to reduce autoimmune response and decrease disease severity in mouse models of SLE. Herein, we review EPO’s non-erythropoietic effects, with a special focus on immune modulating effects in SLE and its potential clinical utility.